From Cool Idea to Evidence-Based Pedagogy: Engaging in Strategic Design, Implementation, Assessment, and Publication of High-Impact Practices - Evans, Sara; Evans, Jocelyn (Experiential Learning and Teaching in Higher Education, 2025)
This guide accompanies a comprehensive toolkit aimed at equipping faculty with the skills and resources necessary to implement a HIP project and produce scholarship from it. Through practical application related to designing, implementing, assessing, and publishing on high impact practice, the use of this guide and toolkit can result in a ready-to-use "project in a box." Higher education professionals with some foundational knowledge of HIP design, implementation, and assessment should find this resource to be grounded in best practices. However, we believe that the strategic thinking underlying this framework is ready to use by anyone building HIPs into curricular and cocurricular offerings. At the end of the day, the primary goal in the development of a HIP should be to provide a transformative experience for our students. That being said, high-impact practices often require more time and effort than preparation of traditional classroom experiences. Therein lies a major tension for faculty interested in being involved in this type of pedagogy. We hope that this resource can be a small support in making that easier, and therefore open up more opportunities for students to benefit from these experiences.